Unified control of DC-DC buck converter using dynamic adaptive controller for battery operated devices - Kanimozhi Kannabiran; Shunmugalatha Alagarsamy (Revista Facultad de Ingeniería Universidad de Antioquia, 2016)
The  objective  of  this  paper  is  improving  the  dynamic  response  of  DC-DC  converter  system  with  internal  parameter  uncertainties.  The  methodology  of  sliding  mode  control  in  existing  works  is  based  on  Proportional  Integral  and  Derivative  Controller  (PID).  The present work addresses various issues on a unified approach for design and application of pulse-width modulation (PWM) based on Digital Adaptive Sliding Mode equivalent (ASM) control technique to buck converter for mobile phones operating in continuous conduction mode (CCM), and discontinuous conduction mode (DCM). The controller is gain scheduled to monitor the output loading condition, and adaptively changes the control parameters to give an  optimum  dynamic  performance  corresponding  to  any  load  variations.  Further  stability  is  analytically  verified  using  Lyapunov  stability  criterion  and  the  system  is  proved  to  be  globally asymptotically stable. Finally, the effectiveness of the proposed method is verified by simulation and experiment. Stable steady state response with reduced ripple is obtained.